(untitled) (Research, Society and Development, 2023)
Objective: To identify the evolution of cases of serious work accidents in motorcyclists injured by traffic accidents in Brazil. Methodology: Epidemiological cross-sectional exploratory study of Serious Work Accidents (ATG), in motorcyclist workers, in Brazil from 2009 to 2018. Results: Sample studied included 9,752 workers, who were involved in a serious accident at work, and that this accident was also characterized as a traffic accident, of these, 10.20% evolved to cure, 82.13% evolved to temporary disability, for 3.76% of those involved the evolution was permanent disability and death was the outcome of 3.9%. Conclusion: It is expected that the results presented in this study can broaden the discussion in search of more specific actions and strategies so that these workers can be reached. And yet, it can contribute and subsidize in the discussions on the subject, well as, stimulate the accomplishment of other studies expanding the understanding on the subject.